Abstracts of theses and dissertations on Philippine mass communication, 1974-1980 - De Jesus, Emilinda Villanueva 1939-
Based on the results of a survey of mass communication courses offered in larger colleges and universities in Metro Manila, a bibliographic search for theses dealing on all aspects of communication was conducted utilizing available library catalogs, bibliographies and indexes of the selected institutions, as well as the records of its graduate schools and research/publications offices.